Cultural Sensitivity in Teaching English: A Focus on Incorporating Uzbek Culture in EFL Classrooms - Norpoʻlatova Nozima Yusufxon qizi (NEW SCIENTIFIC PERSPECTIVES AT THE INTERSECTION OF LANGUAGE, CULTURE, AND TECHNOLOGY, 2025)
In today’s increasingly interconnected world, English as a Foreign Language (EFL) teaching is not just about imparting linguistic skills; it also involves promoting cultural awareness and sensitivity. When English language learners (ELLs) are taught solely through the lens of a Western perspective, it can lead to a disconnection between the learners' own cultural backgrounds and the language they are learning. For Uzbek learners, incorporating their native culture into English language instruction is essential for creating a more relevant and effective learning experience. This article explores the importance of cultural sensitivity in EFL classrooms, specifically in the context of Uzbekistan, and discusses the benefits of integrating Uzbek cultural elements into English language instruction.